DAMPAK SAMPAH LIMBAH RUMAH TANGGA TERHADAP KESEHATAN LINGKUNGAN - Gunawan Widjaja; Savira Lovianda Gunawan (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Garbage is one of the problems in the environment and therefore needs to be managed properly. This study intends to explain the effect of household waste on environmental health and its handling. This research is a normative juridical research that uses secondary data with qualitative analysis.